Direct MOCVD Growth of Iron Oxide on Three‐Dimensional Nickel Foam as Electrode for the Oxygen Evolution Reaction. Issue 22 (30th September 2020) - Stienen, Christian; Bendt, Georg
Abstract: Iron oxide thin films were grown directly on three‐dimensional nickel foam via metalorganic chemical vapor deposition (MOCVD) in the temperature range of 250–450 °C using Fe(CO)5 as precursor. Iron oxide (α‐Fe2 O3 ) films were formed at low substrate temperatures (250–350 °C), whereas the additional growth of an underlying NiO film occurred at substrate temperatures above 350 °C. The electrochemical activities of the as‐formed binder‐free and noble metal‐free electrodes were tested for the oxygen evolution reaction (OER) in alkaline media. An overpotential reduced by 250 mV at a current density of 50 mA cm −2 and a lower Tafel slope of 55 mV dec −1 compared to bare nickel foam were found for the best‐performing electrocatalyst, while the long‐term stability of the as‐formed electrodes was proven by chronopotentiometry. The surface morphology of the iron oxide films was characterized by scanning electron microscopy, whereas the crystallographic phase as well as the elemental composition were determined by X‐ray diffraction, energy‐dispersive X‐ray spectroscopy, X‐ray photoelectron spectroscopy, and time‐of‐flight secondary ion mass spectrometry in the pre‐ and the post‐catalytic state. Abstract : Electrocatalysts from the gas phase : α‐Fe2 O3 thin films are grown via metalorganic chemical vapor deposition on three‐dimensional Ni foam as sustainable and earth‐abundant electrocatalyst for the oxygen evolution reaction in alkaline media.